Factors Influencing Thai People’s Decisions to Rely on Informal Loans due to the Coronavirus Outbreak - Tanomchat, Wichyada (Journal of Applied Economics and Management Strategy, 2023)
This research examined factors that affected the decisions to borrow money outside financial institution system. The sample was determined using a multi-stage sampling method, with the first step being stratified sampling at the regional level. The sample was then divided according to income level and nature of borrowing. It consisted of 900 samples of formal, informal and non-borrowing loans and used estimates using Probit Regression Analysis. The results of the study found that the average monthly income levels after the outbreak of the Coronavirus, having savings, education level, were factors which influenced the borrowing of loans. Other factors effecting borrowing loans involved these following factors: the impact on employment status after the coronavirus outbreak of furloughs with reduced pay, suspension from work without pay, being fired/laid off work with severance pay, being fired/laid off work without compensation, closing the business of the person who was the owner of the business and decreased sales for those whose occupations involved trading in goods and/or services. These factors were related to the decisions to borrow money outside the system. The results of this study can be used as a guideline for the government sector in determining appropriate policies or measures to deal with the problem of informal debt in Thai society, such as changing the law on compulsory education levels to be as high as the associate or degree level, Bachelor’s Degree or equivalent, supporting the provision of additional scholarships to qualified persons across the country, providing additional subsidies to educational institutions that can lead to lower tuition fees for students, promoting people in the country to be aware of the benefits and importance of saving money, developing workers to have high skills and work skills and be more diverse in order to increase opportunities to raise the income level of workers in Thailand, and supporting specialized financial institutions (SFIs) and commercial banks to issue low-interest loans for SMEs facing problems from the Coronavirus outbreak and extending remedial measures for workers and entrepreneurs affected by the problems from the Coronavirus outbreak.